2013
DOI: 10.3390/en6126255
|View full text |Cite
|
Sign up to set email alerts
|

How Efficient are Agitators in Biogas Digesters? Determination of the Efficiency of Submersible Motor Mixers and Incline Agitators by Measuring Nutrient Distribution in Full-Scale Agricultural Biogas Digesters

Abstract: Abstract:The goal of this work was to evaluate the efficiency of two different agitation systems by measuring the nutrient distribution in a digester fed with renewable energy crops and animal manure. The study was carried out at the practical research biogas plant of Hohenheim University. A unique probe sampling system has been developed that allows probe sampling from the top of the concrete roof into different parts and heights of the digester. The samples were then analyzed in the laboratory for natural fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(37 citation statements)
references
References 17 publications
(21 reference statements)
2
30
0
1
Order By: Relevance
“…In the case of perfect mixing and distribution, uniformity in volume distribution must be achieved. These findings are in accordance with results from Lemmer et al (2013), who found that VFAs in the digester substrate are also not distributed evenly. Although Kusch et al (2008) report floating layers in BGP fed with large amounts of fibrous material, our results show that only 6.7-13.1% of the total particle volume are of a particle size >4 mm.…”
Section: Resultssupporting
confidence: 95%
See 1 more Smart Citation
“…In the case of perfect mixing and distribution, uniformity in volume distribution must be achieved. These findings are in accordance with results from Lemmer et al (2013), who found that VFAs in the digester substrate are also not distributed evenly. Although Kusch et al (2008) report floating layers in BGP fed with large amounts of fibrous material, our results show that only 6.7-13.1% of the total particle volume are of a particle size >4 mm.…”
Section: Resultssupporting
confidence: 95%
“…1c) for invasive sampling from the top of the digester is unique in a full-scale BGP. It is designed to take samples from different positions and heights in the digesters through the gas-phase from the fermenting substrate with consideration of all safety and environmental precautions as described by Lemmer et al (2013). The samples (n = 24) were taken at both digesters and deep frozen (À18°C) until further analysis.…”
Section: Sample Collection and Wet Sievingmentioning
confidence: 99%
“…The solid substrate was supplied by a vertical mixer system into a cross‐flow grinder disintegration unit (Bio‐QZ, MeWa, Gechingen, Germany) and subsequently fed into the digester. Digester 1 is equipped with a submersible motor mixer (4670, ITT Flygt AB, Sweden) and a propeller incline shaft agitator (Biogator HPR 1, REMA, Germany) to ensure a uniform distribution of the feed and heat and to enable gas lift from the fermenting substrate 32.…”
Section: Methodsmentioning
confidence: 99%
“…The research biogas plant, its technical setup, and operation modes have been already fully described . The biogas is produced from a mixture of renewable energy crops (∼ 70 % maximum) as well as liquid and solid manure from animal husbandry (minimum ∼ 30 %) under thermophilic (40.5 ± 1) °C conditions in two digesters of identical construction with a volume of 923 m 3 , respectively.…”
Section: Methodsmentioning
confidence: 99%